In vitro Antioxidant Analysis and Antibacterial Screening of the Methanolic Leaf Extract of Kigelia africana (Lam.) Benth - Abdullahi, M. A. (International Journal of Pharmaceutical & Biological Archive, 2022)
Kigelia africana is a medicinal plant with several attributes and considerable potentials, various parts of the plant are used locally to treat cancer, ulcer, skin diseases, diabetes, bacterial and fungal infections, etc.To investigate the invitro Antioxidant and Antibacterial Screening of methanolic leaf extract of kigelia africana. The percentage of antioxidant activity of leaf extracts of Kigelia was assessed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical assay, reducing power (PR) assay, ferric reducing/antioxidant power assay, and nitric oxide radical scavenging assay. Ascorbic acid was used as a standard antioxidant. Antibacterial activity of the leaf extract was tested against four bacterial strains; Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Salmonella spp. The comparative analysis revealed that DPPH with extract exhibited the most remarkable antioxidant activity. The leaf extract showed maximum activity on P. aeruginosa, S. aureus, and Salmonella spp. and moderate activity on E. coli. The extracts were found to contain alkaloids, saponins, flavonoids, and tannins which were present in high amount. Steroids were present in moderate amount. Cardiac glycosides and anthraquinone were present in trace amount, while volatile oils were totally absent. The gas chromatography–mass spectrometry results reveal the presence of nine compounds in the methanolic leaf extract.